Marketing Strategy Analysis of Smoothie Chips Product - Rusdianto, Andrew Setiawan; Suryaningrat, Ida Bagus; Guntoro, Doni (Food, Agriculture and Natural Resources - NETWORKS, 2025)
The marketing strategy evaluation of smoothie chips was conducted using a SWOT analysis and marketing mix benchmarking (4P) on two main comparison brands, namely Fitbar and Soyjoy, in Sumbersari District, Jember Regency. The main objectives of this study were to identify internal-external factors, analyze the product's competitive position in the dimensions of product, price, distribution, and promotion, and formulate appropriate marketing strategy recommendations. The research method used a qualitative approach (IFAS-EFAS) and quantitative (benchmarking) with a Likert scale questionnaire instrument (1-5) for 100 respondents. The instrument was declared valid and reliable with a Cronbach's α value > 0.70. The analysis results showed an IFAS value of 2.60 and EFAS of 2.85, which placed smoothie chips in the aggressive strategy quadrant. The product stands out in the indicators of natural ingredients (0.338) and uniqueness (0.329), but still lags behind in the aspects of visuals, taste, availability, and intensity of digital promotion. The SWOT analysis and benchmarking recommend implementing an aggressive strategy focused on strengthening brand image through storytelling and influencer collaboration, expanding multichannel distribution, enhancing sensory and packaging quality, and employing a penetration pricing strategy with multipack packaging. Given that the product is still a prototype, these findings are evaluative of initial market perception and require further verification through test marketing.